Soil solarization for mass scale production of arbuscular mycorrhizal fungal inoculum in Indian arid zone - RAO, V A; TARAFDAR, J C (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995 to study the feasibility of large scale multiplication of arbuscularmycorrhizal fungal inoculum using soil solarization. At 0-10 cm maximum soil temperature in solarized plots variedfrom 6-9 0C higher compared to the non-solarized plots. A maximmum temperatUre of 68Â°C was observed at 0-10 cmdepth in dry solarized plot. A significant reduction in the activities of various soil enzymes and micro-organisms wasrecorded in solarized plots coupled with irrigation and application of mustard cake. The effect was less at lowerdepths. The efficacy of summer irrigation and soil solarization combined with mustard cake was found toÂ· eradicateabout 91 % native arbuscular mycorrhizal fungal spores at 0-10 cm. The build up of arbuscular mycorrhizal fungalspores was much better in solarized plots with maximum purity of 89% in solarized plots coupled with irrigation andamendment with mustard cake. The results indicated the possibility of adopting soil solarization for large scalemultiplication of arbuscular mycorrhizal fungi by the farmers/nursery managers.